Ökonomische Resilienz. Fallstudie Pommern - Sagan, Iwona; Masik, Grzegorz (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
This article aims to identify the resilience of the Pomorskie Region in Poland. The analysed region belongs to a group of European regions where the negative impact of the economic crisis has not been distinctively visible. In a unitary state like Poland the resilience of the region to the crisis results to a high degree from the external macroeconomic factors of the country. However some regional features play an important role in strengthening resilience. We analysed socio-economic structures in the context of their significance for the region’s resilience. Walker’s and Salt’s (Resilience Thinking. Sustaining ecosystems and people in a changing world, 2006) resilience attributes were used as a template for the findings. Although it is difficult to determine the level of a region’s resilience in a situation of ongoing and growing recession, some conclusions may be derived from the analysis. One of the most important factors of the Pomorskie Region’s resilience is the diversity of economic and social structures. The community and its social capital is undoubtedly one of the strongest attributes of the regional resilience. The Pomorskie Region’s richness in ecosystem services also strengthens its resilience significantly. Overlaps in governance are mainly connected with the development of institutional embeddedness. However the current lack of governance on the level of the most dynamically developing metropolitan areas is an impediment to more dynamic development. The post-totalitarian tradition of centralised governance continues to negatively influence the tight feedbacks attribute of resilience.